the morphological indicators of the nipples and their relationship with the milk production of the Shami cows in Syria (Damascus University Journal of agriculture sciences, 2021)
Abstract36  Shami cows were used in the Deir Al-Hajar Research Center for Shami Cattle Breeding to analyze the data of the nipple dimensions during the year 2019 to estimate some of the morphological indicators of the nipples and their relationship with the milk production of the Shami cows in Syria and to estimate the phenotypic relationships between the nipple dimensions with each other and with total milk production. The results showed a significant effect (P
Keywords: Shami cattle; nipple dimensions, total and daily milk intake; Syria